Herbal Compound Songyou Yin and Moderate Swimming Suppress Growth and Metastasis of Liver Cancer by Enhancing Immune Function. (September 2016) - Zhang, Quan-Bao; Meng, Xiang-Ting; Jia, Qing-An; Bu, Yang; Ren, Zheng-Gang; Zhang, Bo-Heng; Tang, Zhao-You
Objective . Both the Chinese herbal compound Songyou Yin (SYY) and swimming exercise have been shown to have protective effects against liver cancer in animal models. In this study, we investigated whether SYY and moderate swimming (MS) have enhanced effect on suppressing progression of liver cancer by immunomodulation. Methods . C57BL/6 mice were transplanted with Hepa1-6 murine liver cancer cell lines and received treatment with SYY alone or SYY combined with MS. The green fluorescent protein (GFP)-positive metastatic foci in lungs were imaged with a stereoscopic fluorescence microscope. Flow cytometry was used to test the proportion of CD4 +, CD8 + T cells in peripheral blood and the proportions of CD4 + CD25 + Foxp3 + Treg cells in peripheral blood, spleen, and tumor tissues. Cytokine transforming growth factor (TGF)-β1 level in serum was detected by ELISA. Results . SYY plus MS significantly suppressed the growth and lung metastasis of liver cancer and prolonged survival in tumor-burdened mice. SYY plus MS markedly raised the CD4 to CD8 ratio in peripheral blood and lowered the serum TGF-β1 level and the proportions of Treg cells in peripheral blood, spleen, and tumor tissue. The effects of the combined intervention were significantly superior to SYY or MS alone. Conclusion . The combined application of SYY and MS exerted an enhanced effect on suppressing growth and metastasis of liver cancer by strengthening immunity.